Association between neighborhood disadvantage and children's oral health outcomes in urban families in the Chicago area - Lee, Helen H.; Dziak, John J.; Avenetti, David M.; Berbaum, Michael L.; Edomwande, Yuwa; Kliebhan, Margaret; Zhang, Tong; Licona-Martinez, Karla; Martin, Molly A. (Frontiers in Public Health, 2023)
Purpose: Prevalence of childhood caries in urban Chicago, compared to national and state data suggests that neighborhood context influences oral health. Our objective was to delineate the influence of a child’s neighborhood on oral health outcomes that are predictive of caries (tooth brushing frequency and plaque levels). Methods: Our study population represents urban, Medicaid-enrolled families in the metropolitan Chicago area. Data were from a cohort of participants (child-parent dyads) of the Coordinated Oral Health Promotion (CO-OP) trial at 12 months study participation (N=362). Oral health outcomes included brushing frequency and plaque levels. Participants neighborhood resource levels were measured by the Area Deprivation Index (ADI). Linear and logistic regression were used to measure the influence of ADI on plaque scores and brushing frequency, respectively. Results: Data from 362 child-parent dyads were analyzed. Mean child age was 33.6 months (SD 6.8). Majority of children were reported to brush at least twice daily (n=228, 63%) but mean plaque score was 1.9 (SD 0.7), classified as “poor.” In covariate-adjusted analyses, ADI was not associated with brushing frequency (0.94, 95% CI 0.84-1.06). ADI was associated with plaque scores (0.05, 95% CI 0.01-0.09, p value=0.007). Conclusions: Findings support that neighborhood level factors influence children’s plaque levels. Because excessive plaque places a child at high risk for cavities, we recommend inclusion of neighborhood context in interventions and policies to reduce children’s oral health disparities. Existing programs and clinics that serve disadvantaged communities are well positioned to support caregivers of young children to maintain recommended oral health behaviors.